Experience with PACS in an ATM - Pelikan, E. (IEEE Transactions on information technology in biomedicine)
Legacy local area network (LAN) technologies based on shared media concepts are not adequate for the growth of a large-scale picture archiving and communication system (PACS) in a client-server architecture. First, an asymmetric network load, due to the requests of a large number of PACS clients for only a few main servers, should be compensated by communication links to the servers with a higher bandwidth compared to the clients. Secondly, as the number of PACS nodes increases, the network throughput should not measurably cut production. These requirements can easily be fulfilled using switching technologies. Here asynchronous transfer mode (ATM) is clearly one of the hottest topics in networking because the ATM architecture provides integrated support for a variety of communication services, and it supports virtual networking. On the other hand, most of the imaging modalities are not yet ready for integration into a native ATM network. For a lot of nodes already joining an Ethernet, a cost-effective and pragmatic way to benefit from the switching concept would be a combined ATM/Ethernet switching environment. This incorporates an incremental migration strategy with the immediate benefits of high-speed, high-capacity ATM (for servers and high-sophisticated display workstations), while preserving elements of the existing network technologies. In addition, Ethernet switching instead of shared media Ethernet improves the performance considerably. The LAN emulation (LANE) specification by the ATM forum defines mechanisms that allow ATM networks to coexist with legacy systems using any data networking protocol. This paper points out the suitability of this network architecture in accordance with an appropriate system design.